SISTEM TELEMETRI PEMANTAUAN SUHU LINGKUNGAN MENGGUNAKAN MIKROKONTROLER DAN JARINGAN WIFI - Munarso Munarso; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
Research has been done to make a systems of sensors and telemetry systems for data acquisition the ambient temperature based microcontroller and used Wi-Fi networks. This research also aims to make a computer software telemetry systems that can perform real-time data acquisition ambient temperature. Telemetry monitoring the ambient temperature is very important because it can take measurements remotely and in a place that is not affordable. Research has been carried out by designing, manufacturing, and testing telemetry systems which consists of two main parts: the transmitter and receiver. At the transmitter consist of components LM35, ATmega8535 microcontroller, and Wi-Fi radio. While at the receiver consists of a Wi-Fi receiver and computer. Based on the results of the characterization of the sensors and data acquisition, the dependent between the data obtained by the equation ADC and temperature standard thermometer y = 1.0027x + 0.2801. At the receiver, systems can work in reading data, display data in graphs and store data in the MySQL database systems. From the results of the ambient temperature telemetry systems calibration against standard measuring instrument obtained correlation value of R = 0.9988. So the correlation value obtained from this it can be concluded that the telemetry systems as a whole is functioning properly in the ambient temperature measurement data acquisition. Keywords: temperature, telemetry, microcontroller, temperature sensor LM35, WIZ110SR